2014
DOI: 10.5505/phd.2014.69772
|View full text |Cite
|
Sign up to set email alerts
|

Hermeneutic photography. An innovative intervention in psychiatric rehabilitation founded on concepts from Ricoeur.

Abstract: Bu makale akıl sağlığına ilişkin yorumbilimden, daha spesifik olmak gerekirse Ricoeur'un yorumbiliminden geliştirilip kavramlaştırılmış girişim ve yaklaşımlar hakkındadır. Bu girişime foto-enstrüman diyoruz. Hastaların yaşadıkları dünyadaki deneyimlerinden anlam çıkarma sürecinde hastalara yardımcı araç olarak fotografi kullanılmaktadır. Hastaların yaşamla olan bağlarını güçlendirmeyi ve pekiştirmeyi amaçlar. Öykü anlatmayı kolaylaştırarak bunu başarmayı amaçlar. Ricoeur tarafından yorumlandığı gibi mimezis, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…What we also found was a great need for being recognized as a person, share with others what one feels and thinks and express this. This we had also come across in our earlier research on the therapeutic use of photography [20] and was confirmed again by the observation that having your portrait made was a favorite activity: people lined up for the photographer.…”
Section: Discoversupporting
confidence: 59%
See 1 more Smart Citation
“…What we also found was a great need for being recognized as a person, share with others what one feels and thinks and express this. This we had also come across in our earlier research on the therapeutic use of photography [20] and was confirmed again by the observation that having your portrait made was a favorite activity: people lined up for the photographer.…”
Section: Discoversupporting
confidence: 59%
“…In the project the photographs are made by a professional photographer. However, this may also be done by the caregiver himself or by an amateur-photographer who works as a volunteer or by the client himself (as is the case in the photo-instrument: see Author [20]). The project was continued by volunteers from a photo club in the nearby town.…”
Section: Destinymentioning
confidence: 99%
“…They can stimulate patients to connect with their long term values in life and become aware of the strengths they can use when confronting the challenge of putting their lives in order and start living 'a valued life' . Care professionals could for instance apply techniques such as the Values Compass from Acceptance and Commitment Therapy [15] and use creative interventions such as Hermeneutic Photography [16,17] in order to help patients to (re-)discover their own strengths and values and use them 'to lift a life up from the shackles of illness' [18].…”
Section: Skills and Architectural Adaptationsmentioning
confidence: 99%
“…Also a photo exhibition is organized. The photo stories enabled patients to be recognized and accepted in positive and valuable aspects of their identity and history [5]. This reinforced their self-esteem and made them sensitive to their potential for change, growth and recovery (Figure 1) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The photo stories enabled patients to be recognized and accepted in positive and valuable aspects of their identity and history [5]. This reinforced their self-esteem and made them sensitive to their potential for change, growth and recovery (Figure 1) [5]. We have reported on this psychosocial intervention in a publication, titled: Recovery in Mental Health Care with the Aid of Photo-stories: An Action Research Based on the Principles of Hermeneutic Photography [6].…”
Section: Introductionmentioning
confidence: 99%